Access to Justice in Microfinance An Analytical Framework for Peru - Olteanu, Yasmin (Palgrave Studies in Impact Finance,, 2018)
This book analyzes the whole path to justice: from the decision to enter the path to justice until justice is achieved and applies a mixed-methods approach using quantitative and qualitative data. It deliberately takes the consumer's perspective and, beyond the scope of existing studies, does not only take into account the existence of mechanisms and forums to claim justice, but their appropriateness for vulnerable target groups. The book sheds more light on microfinance and other vulnerable clients who, due to existing barriers, cannot access grievance, redress or complaint mechanisms. Eliminating these access barriers would cater to the achievement of the 16th Sustainable Development Goal by increasing vulnerable consumers' Access to Justice. This book will be of interest to academics researching access to justice, researchers focusing on consumer protection issues in developing countries, and practitioners working in financial inclusion.